Effectiveness of the Application of Economic Tokens to Improve the Academic Self Concept of Students with Developmental Disabilities: Efektivitas Penerapan Token Ekonomi Untuk Meningkatkan Konsep Diri Akademik Siswa Tunagrahita - Muzdalifah, Risnida (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effectiveness of giving economic tokens to improve the academic self-concept of mentally retarded students. The design of this study is multiple-baseline design across the subject that is all research subjects get the same intervention as before it has been ascertained that the research subjects have the same characteristics according to the research objectives. Research participants were 2 people. Data collection techniques in this study used a scale of academic self-concept, observation, and interviews. The results showed that the administration of economic tokens was effective in improving the academic self-concept of retarded students with a significance result of 0.041 <0.05.